Privacy of Internet Users in the Era of Transformative Marketing - Muhammad Farooq; Qasim Ali Qureshi (Journal of Management Practices, Humanities and Social Sciences, 2020)
This research aims to investigate the customer concern of privacy over the internet pertaining to e-commerce companies in the era of transformative marketing. The paper discusses different drivers and challenges of customer's data protection. The article also explores the two prominent prospects on internet privacy; the "consumer protection view" and "free-market view". To carry out the current study, a thorough literature review is done. Recent articles published in high-quality journals relevant to the topic were collected and analyzed for carrying out current study. Based on the review of literature, it can be stated the vast majority of consumers are unaware of how their personal data is used. Consumers are either too careless in managing their data or too cautious, which may lead to problems for all stakeholders. The researchers advocate the consumer protection view. The current article highlights alarming insight that consumers are unaware and unconcerned how their private data is used for commercial gain without taking their permission. The two views on consumer privacy are shared, and future evolution in these views is discussed. The article has also highlighted that the government has to play an active role since the issue pertains to the entire world.